2020
DOI: 10.1021/acs.jmedchem.9b02020
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drug Carbamazepine Binds to a Novel Pocket on the Wnt Receptor Frizzled-8

Abstract: Misregulation of Wnt signaling is common in human cancer. The development of small molecule inhibitors against the Wnt receptor, frizzled (FZD), may have potential in cancer therapy. During small molecule screens, we observed binding of carbamazepine to the cysteine-rich domain (CRD) of the Wnt receptor FZD8 using surface plasmon resonance (SPR). Cellular functional assays demonstrated that carbamazepine can suppress FZD8-mediated Wnt/β-catenin signaling. We determined the crystal structure of the complex at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…F2.A suppresses pancreatic cancer tumor growth in xenograft mouse models. Interestingly, carbamazepine, an antiepileptic drug, was recently reported to bind the cysteine-rich domain of FZD8, which suggests been explored as a promising therapy option in cancers [48]. Additionally, Fz7-21, a selective FZD7-binding peptide, disrupts intestinal stem cells and organoids, implicating the potential of therapeutic application in malignant diseases [49].…”
Section: Wnt/fzd Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…F2.A suppresses pancreatic cancer tumor growth in xenograft mouse models. Interestingly, carbamazepine, an antiepileptic drug, was recently reported to bind the cysteine-rich domain of FZD8, which suggests been explored as a promising therapy option in cancers [48]. Additionally, Fz7-21, a selective FZD7-binding peptide, disrupts intestinal stem cells and organoids, implicating the potential of therapeutic application in malignant diseases [49].…”
Section: Wnt/fzd Antagonistsmentioning
confidence: 99%
“…In addition, researchers had found some old drugs performed new tricks, which play important roles in tumor growth, invasion and metastasis via regulating Wnt/β-catenin signaling pathway. Carbamazepine, an antiepileptic drug, was recently reported to bind the cysteine-rich domain of FZD8, which suggested to been explored as a promising therapy option in cancers [48]. It was also reported that psychiatric agent hexachlorophene attenuated Wnt/β-catenin signaling through suppressing β-catenin degradation in colon cancer cells [111].…”
Section: Natural Agents and New Activity Of Old Drugsmentioning
confidence: 99%
“…FA.2 inhibits pancreatic cancer tumor growth in xenograft models [128], but this inhibitor has also not been tested in gynecologic malignancies. Carbamazapine, an antiepileptic drug, has recently been found to bind the cysteine-rich domain (CRD) of FZD8 [130]. Carbamazapine, an antiepileptic drug, has recently been found to bind the cysteine-rich domain (CRD) of FZD8 [130], suggesting that carbamazapine may be worth exploration as a treatment in gynecologic malignancies.…”
Section: Wnt/fzd Inhibitorsmentioning
confidence: 99%
“…Targeting non-coding RNAs present an additional approach to inhibiting oncogenic pathways or enhancing tumor-suppressive pathways. Challenges of targeting Fzds include lack of high-resolution crystal structures for Fzds and context-dependent associations of individual Wnts and Fzds ( Schulte and Kozielewicz, 2020 ; Zhao et al, 2020 ). Using non-coding RNA to target Fzd activity could circumvent some of these challenges by altering expression, instead of attempting to bind to Fzd receptors or by offering tissue- or disease-specific targeting.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, compounds that bind to the transmembrane domain of Fzd7 and interfere with Wnt binding could reduce oncogenic signaling in many cancer types ( Kalhor et al, 2020 ). The epilepsy drug carbamazepine binds Fzd8 to suppress β-catenin signaling ( Zhao et al, 2020 ), and Fzd9 may be a critical receptor for a lung cancer chemoprevention drug ( Tennis et al, 2010 ). Identifying non-coding RNAs that enhance or inhibit downstream Fzd signaling will support new approaches to cancer prevention and treatment.…”
Section: Introductionmentioning
confidence: 99%